Could an osteoinductor result in degeneration of a neurofibroma in NF1? - Jean-Paul, Steib (Springer-Verlag, 2010)
We report a case of fatal evolution of neurofibromatosis in a young boy. A laminectomy was performed when he was 9 years old. A secondary hyperkyphosis led to many surgeries resulting in recurrent malunions. When he was 23 years old, a breakage of his rods was treated by a new instrumentation and a T12–L1 interbody cage fitted with rh-BMP. Five months later, he developed a huge posterior tumour on his back. The biopsy diagnosed a neurofibrosarcoma. The growth of the tumour was extremely rapid. He died after several months from a septic shock. NF1 is characterised by neurofibromas that have a possibility of malign degeneration and conversion to a sarcoma. However, the chronology, rapidity of evolution and the exceptional volume of the tumour made us wonder whether the BMP had a part of responsibility as osteoinductor in the malignant degeneration, in this particular case, of neurofibromatosis. It seemed important to point out this case to the medical community.